Revegetation and Soil Management Effects on Chemical Properties of a Saprolite Resulting from Deep Soil Removal - Paz-Ferreiro, Jorge; Alves, Marlene Cristina [UNESP] (Taylor & Francis Inc, 2012)
During the building of a hydroelectrical power plant at Ilha Solteira in the Parana River (Brazil), materials of a highly weathered soil Oxisol were extracted from a depth between 5 and 8 m for engineering works. This resulted in an abandoned depression area. The topsoil was not salvaged and the open pit was not backfilled, and as result vegetation hardly or not at all recovered. on the residual saprolite materials, an experimental field was established to assess different soil rehabilitation treatments. Field experiments were initiated in 1992. After soil tillage, two different crops and three different liming strategies were compared, giving six combinations. In addition, two uncropped control treatments, tilled and no-tilled, were established so that a total of eight treatments were assessed. The experimental design consisted of four randomized experimental blocks, which included a total of 32 plots with a plot area of 100 m(2). This experiment was used to study the effectiveness of the soil-reclamation treatments after a 9-year period. Soil samples were taken at three different depths (0-10, 10-20, and 20-40 cm), and they were analyzed routinely for pH, organic-matter content, and cation exchange capacity (CEC). Revegetation of the abandoned saprolite material increased soil organic-matter content and cation exchange capacity (CEC), and to some extent small differences between treatments were evidenced. Exchangeable calcium (Ca) and magnesium (Mg) recovered faster than organic-matter content. A significant linear relationship was found between organic-matter content and CEC, suggesting continued addition of organic material will further approach the value of these parameters to those levels corresponding to natural soils under "Cerrado" vegetation.
Keywords: Amendment; CEC; organic matter; Oxisol; profile decapitation; revegetation